K–12 Technology Accessibility: The Message From State Governments. Issue 2 (June 2018) - Shaheen, Natalie L.; Lazar, Jonathan
This study examined state education technology plans and technology accessibility statutes to attempt to answer the question—is K–12 instructional technology accessibility discussed in state-level technology accessibility statutes and education technology plans across the 50 United States? When a K–12 school district is planning the construction or acquisition of a new digital technology, are the legal requirements for making that digital environment accessible to people with disabilities part of the decision process? Just like built environments, digital environments can either be accessible or inaccessible to people with disabilities; the digital environment can either support or impede the inclusion of people with disabilities. At the federal level, statutes, regulations, and policy guidance make it clear that technology must be accessible to students with disabilities in K–12 schools. The message from the federal government is consistent. But what messages are state governments communicating, through statutes and policies, to K–12 educators about technology accessibility?